Replication Data for: Herbivory and warming have opposing short-term effects on plant-community nutrient levels across high-Arctic tundra habitats - Petit Bon, Matteo; Bråthen, Kari Anne; Ravolainen, Virve Tuulia; Böhner, Hanna; Jónsdóttir, Ingibjörg Svala (DataverseNO, 2017)
Dataset used to ask to what extent plant-community nutrient levels (concentrations and pools of nitrogen and phosphorus) are affected by herbivory (spring goose grubbing) and warming (higher summer temperatures) in high-Arctic tundra (Svalbard).